THE USE OF SOCIAL MEDIA IN LEARNING ENGLISH VOVABULARY - Afiah P., Nur; Atmowardoyo, Haryanto; Sakkir, Geminastiti (State University of Makassar, 2022)
This study aims to describe how the use of social media in the process of learning English vocabulary. This study uses a qualitative method using a descriptive approach. To achieve the research objectives, data were obtained through observations and interviews. The participants included in this study were 25 students of class VIII.A SMPN 03 Mattiro Sompe Kab. Pinrang as who have passed the required criteria (cluster random sampling). The results of this study indicate that social media can be used as, (1) learning medium because it is easily accessible. (2) as an information source for teachers and students (3) Increase students' motivation in learning English. (4) Increase students' vocabulary to make it easier for students to learn English. (5) Get used to listening and reading English words on social media. (6) Whataapp and YouTube are used as media alternatives in English learning.Keywords- Using, Social Media, WhatsApp and YouTube, Learning Media, Vocabulary.